THE UTILIZATION OF IDENTIFICATION TABLE MEDIA TO IMPROVE THE STUDENTS OFFICIAL LETTER - SYAMSIA, SYAMSIA; SUDARMIN, SUMIYATI (LINGUISTICA, 2024)
The objectives of this research were to find out whether the identification table media in official letters to improve the students™ writing in formal letter and to know the difficulties of the students™ deals with in writing formal letter. Writing is an activity to express feelings, ideas, ideas, or opinions in writing aimed at others by paying attention to linguistic rules indirectly (Andira, Adnan, & Yamin, 2017). One of the important functions of writing skills is the ability to write formal letters ( (Sitiulwiah & Baisu, 2018)). Formal letter is a letter used for formal purposes by certain parties, be it individuals, institutions, organizations, or certain agencies to communicate with each other formally ( (Suprapto, 2018). The research used in this research is non-experimental quantitative research that uses descriptive methods. The populations in this research were the students of English Department; the sample of this research was 15 students in fifth semester. . To collect the data, the researcher used documentation and interview. The data is analyzed by using the thematic content analysis. The result of this research, It can be seen from the students™ scoring of post training test is higher than pre training test; there is an improvement of students™ writing formal letter by using identification table media. Beside the students™ score, the students also give the good responses in writing formal letters using identification table media. The students™ difficulties in writing formal letter can be help by using identification table media